Analisis Kinerja Perusahaan (Kasus Bank X Jakarta) - Rudi Bratamanggala (Jurnal Manajemen FE-UB, 2014)
This research is a quantitative study using survey research methods to the population. Respondents data were tested using the test of assumptions of classical instruments. Data were analyzed using descriptive statistics and inferential statistics with multiple linear regression analysis. Multiple correlation analysis and determination analysis used in order to see the relationship and influence of independent variables to the dependent variable. Independent variables in this study is organizational culture, leadership, and motivation, while the dependent variable is performance. This research tests the hypothesis using simultaneous and partial.Based on the results of research and the discussion shows there is a significant variable influences organizational culture, leadership, and motivation integratedly on the performance of employees of PT. Bank X Tbk Jakarta Branch, it can be seen from the results of F test with the significant/probability (0.000) <α (0.05) and Fhitung (9.274)> Ftabel (2.883), these results shows that integratedly the organizational culture, leadership, and motivation have a significant effect on performance. Multiple regression equation was Y = 11.916 + 0.576 X1 + 0.086 X2 + 0.078 X3. The value R = 0.863, which means the influence of organizational culture, leadership and motivation integratedly have a very strong relationship to performance. Determination/R2 coefficient = 0.745, this value can be defined that 74.5% of performance variables can be explained by organizational culture, leadership, and motivation integratedly, the remaining 25.5% of the other variables not included in the research.